Understanding Long-Run African Growth: Colonial Institutions or Colonial Education? - (:unkn) unknown (My University, 2008)
Long-term growth in developing countries has been explained in four frameworks: ‘extractive colonial institutions' (Acemoglu et al., 2001), ‘colonial legal origin' (La Porta et al., 2004) ‘geography' (Gallup et al., 1998) and ‘colonial human capital' (Glaeser et al., 2004). In this paper we test the ‘colonial human capital' explanation for sub-Saharan Africa, controlling for legal origins and geography. Utilizing data on colonial-era education, we find that instrumented human capital explains long-term growth better, and shows greater stability over time, than instrumented measures for extractive institutions. We suggest that the impact of the disease environment on African long-term growth runs through a human capital channel rather than an extractive-institutions channel. The effect of education is robust to including variables capturing legal origin and geography, which have additional explanatory power.
Keywords: African Research